1995
DOI: 10.1016/s0266-7681(05)80164-0
|View full text |Cite
|
Sign up to set email alerts
|

Absorbable Sutures in Tendon Repair

Abstract: The risks of foreign implantation may be avoided in tendon repair by the use of absorbable sutures, for example polydioxanone. In this study, the in vivo tensile strength half-life of 4/0 polydioxanone was found to be approximately 4 weeks. Using a rabbit model, we compared polydioxanone tendon repairs with polypropylene tendon repairs. Unilateral flexor digitorum longus repairs were performed on 46 rabbits using either polydioxanone or polypropylene. Tendons were harvested at 3 days, 2 weeks and 4 weeks and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(13 citation statements)
references
References 3 publications
0
12
0
1
Order By: Relevance
“…Compared to nonabsorbable sutures, the use of absorbable sutures may avoid problems associated with long-term foreign body implantation such as excessive fibrosis and stitch granuloma, but maintaining adequate tensile strength during the early reconstruction period remains a challenge due to their absorption into the body [3,5]. Thus, using absorbable sutures has been controversial.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Compared to nonabsorbable sutures, the use of absorbable sutures may avoid problems associated with long-term foreign body implantation such as excessive fibrosis and stitch granuloma, but maintaining adequate tensile strength during the early reconstruction period remains a challenge due to their absorption into the body [3,5]. Thus, using absorbable sutures has been controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Monofilament fiber PDS has been recently used for flexor tendon repairs. The results of an animal experiment reported by O'Broin [5] showed that PDS was not only flexible and strong, but also had high breaking strength and minimal foreign body reaction. PDS retained its breaking strength for 9 weeks, which is a relatively long time.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations